2022
DOI: 10.3390/ani12131609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacillus licheniformis on Growth Performance, Diarrhea Incidence, Antioxidant Capacity, Immune Function, and Fecal Microflora in Weaned Piglets

Abstract: Bacillus licheniformis (B. licheniformis) is a safe probiotic that can promote animal growth and inhibit pathogenic bacteria. This study aimed to assess the effects of B. licheniformis, one green feed additive, on growth performance, diarrhea incidence, immune function, fecal volatile fatty acids, and microflora structure in weaned piglets. Weaned piglets (n = 180) were randomly divided into three treatment groups and fed a basal diet and a basal diet supplemented with 500 mg B. licheniformis per kg and 1000 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 53 publications
4
10
0
1
Order By: Relevance
“…We found that dietary supplementation with LG increased the activities of SOD in the ileum and CAT in the colon and decreased the contents of MDA in the jejunum and ileum and H 2 O 2 in the jejunum. These results are consistent with Yu et al‘s study that supplementation of 500 mg/kg B. licheniformis in the diet of weaned piglets enhanced antioxidant capacity [ 44 ]. In summary, dietary supplementation of 0.6% LG enhanced the antioxidant capacity of the intestine by regulating the expression of antioxidant-related genes and increasing the activity of intestinal antioxidant enzymes.…”
Section: Discussionsupporting
confidence: 93%
“…We found that dietary supplementation with LG increased the activities of SOD in the ileum and CAT in the colon and decreased the contents of MDA in the jejunum and ileum and H 2 O 2 in the jejunum. These results are consistent with Yu et al‘s study that supplementation of 500 mg/kg B. licheniformis in the diet of weaned piglets enhanced antioxidant capacity [ 44 ]. In summary, dietary supplementation of 0.6% LG enhanced the antioxidant capacity of the intestine by regulating the expression of antioxidant-related genes and increasing the activity of intestinal antioxidant enzymes.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, studies have revealed that supplementation with B. licheniformis improves growth performance and modulates digestive microflora [8,10]. Studies have also confirmed an improvement in the antioxidant capacity induced by dietary B. licheniformis in pigs and poultry [11][12][13]. B. licheniformis can play a positive role in defending against necrotic enteritis by modulating the intestinal microflora.…”
Section: Introductionmentioning
confidence: 90%
“…15 Our previous studies demonstrated that B. licheniformis HJDY01 improved growth performance, immunity, and antioxidant function in broilers, 16 and relieved diarrhoea, increased immunity, and improved faecal microflora structure in weaned pigs. 17 At present, comprehensive studies on the efficacy and mechanism of B. licheniformis HJDY01 against NE in broilers are scarce. NE occurs most frequently in 16-to 28-day-old birds.…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus licheniformis has displayed strong environmental adaptability based on its high temperature resistance, acid resistance and bile salt resistance 15 . Our previous studies demonstrated that B. licheniformis HJDY01 improved growth performance, immunity, and antioxidant function in broilers, 16 and relieved diarrhoea, increased immunity, and improved faecal microflora structure in weaned pigs 17 …”
Section: Introductionmentioning
confidence: 99%